Joint Preservation in the Adult Knee - Rodríguez-Merchán, E. Carlos; Liddle, Alexander D. (Springer International Publishing : Imprint: Springer, 2017)
This book offers a comprehensive overview of the basic science and clinical evidence for non-arthroplasty interventions in the adult knee. It aims to cover all aspects of joint-preserving knee surgery, from injectable therapies such as platelet-rich plasma and stem cell therapies to surgical interventions such as meniscal repair and replacement, ligament reconstructions, and osteotomies. Following discussion of clinical assessment and imaging, individual chapters focus on specific clinical problems, including patellofemoral joint disorders, chondral injuries, and bone tumors. For each condition, a thorough overview is provided, describing clinical assessment, management (including surgical and non-surgical methods), and novel therapies. The contributors are experts in their fields from across Europe and are drawn from the worlds of clinical and academic orthopedic surgery. This book is unique in its coverage of the entire span of non-arthroplasty knee surgery and its focus on both clinical and basic science aspects. It will be helpful for knee surgeons and those engaged in research on knee-related topics, but also for students and other physicians involved in the care of patients with disorders of the knee. .
Keywords: Medicine.; Rheumatology.; Orthopedics.; elektronické knihy; electronic books